Comparative Proteomics Study of Outer Membrane Proteins from three Pathogenic Leptospira Species used in Vaccine - Aghaiypour Kolyani, Khosrow; Shokri, Rahman (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Background and Objective: Outer Membrane Proteins (OMPs) have an important role in pathogenecity and immunogenecity of Leptospira introgans. The aim of this study was chemical and immunological analysis of OMP extracted from three vaccinal strains of pathogenic Leptospira (L. canicola, L. grippotyphosa & L. sejroae hardjo) by electrophoresis and western blotting. Materials and Methods: Outer membrane enriched fractions that are insoluble in sodium N- lauryl sarcosinate isolated and studied by Sodium dodecyl sulfate polyacrylamide gel electrophoresis. For identifying of antigenic properties of different proteins in three strains, antiserums developed in rabbit against the whole three valent vaccine and also specific OMPs rom each of three Leptospira strains. The antiserum was used for immunological studies with immuno double diffusion and western blotting. Results: in SDS-PAGE five common protein bands with approximate molecular masses of 75,36,25,23 and 19 KDa were identified. After western blot studies identified four or five immunogenic band. In general, antiserum against L. grippotyphosa OMP has the highest ability in detecting common bands between three strains. Conclusion: Chemical and immunological comparisons between OMPs of the three strains which are being used in the commercial vaccine, provided useful documents to assess and maybe improve vaccine quality. It indicated that OMPs are one of the major Leptospira component contributing in immunity and protectivity. Comparison between individual OMPs of each serotype revealed that L. grippotyphosa ones could contribute more in vaccine induced protectively in comparison with the other two serotypes.